The Influence of Investment Decisions, Funding Decisions, and Profit Margins on Firm Value in Banking Companies Listed on the Indonesian Stock Exchange - Sari, Maya; Mathewi, Mathewi (Lembaga Riset Ilmiah, 2023)
The purpose of this research is to determine the influence of investment decisions on firm value, to determine the influence of funding decisions on firm value, to determine the influence and profit margin on firm value, and to determine the influence of investment decisions, funding decisions and profit margins on firm value in banking companies listed on the Indonesian Stock Exchange. The population in this research is 46 banking companies registered on the IDX, with research samples from 26 companies with five years of observation and 145 samples. The data collection technique is in the form of documentation. The analysis technique in the research uses the SPSS application, which is used for descriptive statistics, multiple linear regression analysis, partial Tests, and determinant tests. The research results show that investment decisions have a positive and significant influence on firm value, funding decisions have a negative and significant influence on firm value, the profit margin has no influence on firm value of banking companies listed on the Indonesian Stock Exchange